Human hepatic stellate cell lines, LX-1 and LX-2: new tools for analysis of hepatic fibrosis. Issue 1 (10th December 2004) - Xu, L; Hui, A Y; Albanis, E; Arthur, M J; O'Byrne, S M; Blaner, W S; Mukherjee, P; Friedman, S L; Eng, F J
Abstract : Background: Hepatic stellate cells (HSCs) are a major fibrogenic cell type that contributes to collagen accumulation during chronic liver disease. With increasing interest in developing antifibrotic therapies, there is a need for cell lines that preserve the in vivo phenotype of human HSCs to elucidate pathways of human hepatic fibrosis. We established and characterised two human HSC cell lines termed LX-1 and LX-2, and compared their features with those of primary human stellate cells. Methods and results: LX-1 and LX-2 were generated by either SV40 T antigen immortalisation (LX-1) or spontaneous immortalisation in low serum conditions (LX-2). Both lines express α smooth muscle actin, vimentin, and glial fibrillary acid protein, as visualised by immunocytochemistry. Similar to primary HSCs, both lines express key receptors regulating hepatic fibrosis, including platelet derived growth factor receptor β (βPDGF-R), obese receptor long form (Ob-RL ), and discoidin domain receptor 2 (DDR2), and also proteins involved in matrix remodelling; matrix metalloproteinase (MMP)-2, tissue inhibitor of matrix metalloproteinase (TIMP)-2, and MT1-MMP, as determined by western analyses. LX-2 have reduced expression of TIMP-1. LX-2, but not LX-1, proliferate in response to PDGF. Both lines express mRNAs for α1(I) procollagen and HSP47. Transforming growth factor β1 stimulation increased their α1(I) procollagen mRNA expression, as determined by quantitative reverse transcription-polymerase chain reaction. LX-2, but not LX-1, cells are highly transfectable. Both lines had a retinoid phenotype typical of stellate cells. Microarray analyses showed strong similarity in gene expression between primary HSCs and either LX-1 (98.4%) or LX-2 (98.7%), with expression of multiple neuronal genes. Conclusions: LX-1 and LX-2 human HSC lines provide valuable new tools in the study of liver disease. Both lines retain key features of HSCs. Two unique advantages of LX-2 are their viability in serum free media and high transfectability.